From cylindrical to non‐cylindrical foreland basin: Pliocene–Pleistocene evolution of the Po Plain–Northern Adriatic basin (Italy). (14th June 2019) - Amadori, Chiara; Toscani, Giovanni; Di Giulio, Andrea; Maesano, Francesco Emanuele; D'Ambrogi, Chiara; Ghielmi, Manlio; Fantoni, Roberto
Abstract: The architecture of foreland basins and the resulting distribution of clastic sediments are related to the constant interplay between tectonics and sedimentation. Specifically, basin floor modifications strongly influence dimensions, continuity and connections of sand‐size and fine‐grained deposits. Given the increasing need to identify deep potential reservoir deposits, the large‐scale definition of clastic porous targets and their seals is a matter of interest for oil and gas industry. Here, we present the reconstruction of the Po Plain and Northern Adriatic Foreland Basin (with an extent of ca. 40, 000 km 2 ) and its Pliocene–Pleistocene evolution, as an example of a sedimentary clastic system controlled by strongly non‐cylindrical foreland geometry. The study is based on the basin‐scale mapping of six unconformity‐bounded sequences, performed by interpreting a dense network of seismic lines and correlating well‐log data. This provides a three‐dimensional model of the step‐by‐step evolution of the basin and a description of the sediment dispersal pattern. We found that the basin records the change from a continuous (cylindrical) to highly fragmented (non‐cylindrical) foredeep geometry during Late Pliocene. In the Northern Apennines case, the main factors driving the development of a non‐cylindrical geometry are mainly related to inherited inhomogeneity in the downgoing block linked to its Mesozoic extensional faulting, and the relative orientation of these lineaments with respect to the direction of orogen migration. During the late Pliocene–Pleistocene the two directions progressively became close to parallel, and the Northern Apennines system reacted changing from a cylindrical to a non‐cylindrical state.